2018
DOI: 10.12659/ajcr.908252
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillar Small Cell Carcinoma: Potential Contribution of Human Papillomavirus

Abstract: Patient: Female, 64Final Diagnosis: Small cell carcinoma of the tonsilSymptoms: Sore throatMedication: —Clinical Procedure: —Specialty: OncologyObjective:Unknown ethiologyBackground:Extrapulmonary small cell carcinoma (SmCC) is a relatively rare clinical entity constituting only 2.5–5% of SmCCs. Recently, evidence has emerged that high-risk types of human papillomavirus (HPV) might play an etiologic role in oropharyngeal SmCC, similar to squamous cell carcinoma.Case Report:Here, we present a case of tonsillar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…HPV‐related small cell carcinoma of the oropharynx is a newly recognized variant with few cases reported in the literature . This study presents one of the first comprehensive cytologic characterizations of this entity and includes 6 patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HPV‐related small cell carcinoma of the oropharynx is a newly recognized variant with few cases reported in the literature . This study presents one of the first comprehensive cytologic characterizations of this entity and includes 6 patients.…”
Section: Discussionmentioning
confidence: 99%
“…HPV-related small cell carcinoma of the oropharynx is a newly recognized variant with few cases reported in the literature. [13][14][15][16][17][18][19] This study presents one of the first comprehensive cytologic characterizations of this entity and includes 6 patients. Overall, the presentation and clinical course of these tumors were similar to those in previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Review of the literature revealed 30 patients with OPSmCC for which p16 and/or HPV testing (by ISH and/or polymerase chain reaction [PCR]) have been done (Table 1). 5,6,[13][14][15][16][17][18][19][20][21][22] The ages of the patients ranged from 35 to 83 years with a mean age of 63 years. There is a male predominance with a 3.3:1 male to female ratio.…”
mentioning
confidence: 99%